2013
DOI: 10.1093/cid/cit571
|View full text |Cite
|
Sign up to set email alerts
|

A New Strategy for Healthcare-Associated Pneumonia: A 2-Year Prospective Multicenter Cohort Study Using Risk Factors for Multidrug-Resistant Pathogens to Select Initial Empiric Therapy

Abstract: Japan Medical Association Center for Clinical Trials, JMA-IIA00054.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
89
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(94 citation statements)
references
References 32 publications
2
89
1
2
Order By: Relevance
“…21,22 An alternative approach for classifying patients with COP is to identify the number of risk factors for MDR infection they have in order to better direct the use of broad-spectrum antibiotics. 23 Our study found that NOTE. ICU, intensive care unit.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…21,22 An alternative approach for classifying patients with COP is to identify the number of risk factors for MDR infection they have in order to better direct the use of broad-spectrum antibiotics. 23 Our study found that NOTE. ICU, intensive care unit.…”
Section: Discussionmentioning
confidence: 64%
“…Scoring systems to identify patients with MDR infections, including MDR P. aeruginosa, are available but limited in their overall ability to predict MDR infection. 23,36,37 A number of novel methods aimed at improving the early identification of pathogens and related antibiotic susceptibilities are also entering the diagnostic arena. Such technological advances offer a strategy that could potentially maximize the administration of appropriate antibiotic therapy while minimizing unnecessary antibiotic exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Several other risk factor models have been developed as outlined in Table 1 [7][8][9][10][11][12]. These algorithms were locally developed by investigators, often with the assistance of outside experts, with the primary goal of improving upon the identification of patients with pneumonia attributed to antibiotic-resistant bacteria.…”
mentioning
confidence: 99%
“…In hospital setting, it is widely associated with nosocomial infection (Idris et al 2012). Over the years, the isolation of multidrug-resistant P. aeruginosa (MDRPA) isolates from hospitalized patients has been increasingly reported, especially in the critically ill patients (Aloush et al 2006;Hsu et al 2005;Maruyama et al 2013;Padmakrishnan et al 2009). This leads to the severe adverse outcomes of the infection due to limited availability of antimicrobial agents for treatment.…”
Section: Introductionmentioning
confidence: 99%